2017
DOI: 10.1007/s00221-017-5154-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of non-numerical domains on space: a systematic review and meta-analysis

Abstract: The spatial numerical association of response code (SNARC) effect is characterized by low numbers mapped to the left side of space and high numbers mapped to the right side of space. In addition to numbers, SNARC-like effects have been found in non-numerical magnitude domains such as time, size, letters, luminance, and more, whereby the smaller/earlier and larger/later magnitudes are typically mapped to the left and right of space, respectively. The purpose of this systematic and meta-analytic review was to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 65 publications
11
41
1
Order By: Relevance
“…Thus, the SNARC effect should prove to be a SQUARC (Spatial Quantity Association of Response Codes) effect. The nonsymbolic aspects of the current experiments parallel other research demonstrating that the basic operation of the SNARC effect does apply to nonsymbolic magnitudes, such as physical size, luminance, angle magnitude, and loudness (see Macnamara, Keage, & Loetscher, for a review). However, the use of ratio magnitudes in this study represents a major departure from previous nonsymbolic studies involving associations of space and magnitude.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, the SNARC effect should prove to be a SQUARC (Spatial Quantity Association of Response Codes) effect. The nonsymbolic aspects of the current experiments parallel other research demonstrating that the basic operation of the SNARC effect does apply to nonsymbolic magnitudes, such as physical size, luminance, angle magnitude, and loudness (see Macnamara, Keage, & Loetscher, for a review). However, the use of ratio magnitudes in this study represents a major departure from previous nonsymbolic studies involving associations of space and magnitude.…”
Section: Discussionsupporting
confidence: 75%
“…Similarly, space-reward associations across laterality have been found when processing reward-related words, showing faster responses under congruent conditions (monetary gain -dominant right hand; monetary loss -non-dominant left hand) than under incongruent ones (monetary gain -non-dominant left hand; monetary lossdominant right hand; Vicario and Rumiati, 2014). For further spatial-associations across laterality (e.g., luminance, size, letters) see also a review by Macnamara et al (2018).…”
Section: Valence Associations Across the Lateral Space: The Affectivementioning
confidence: 85%
“…In a typical SNARC effect, people respond faster to smaller numbers with the left hand and to larger numbers with the right, indexing a left-to-right mental number line. Beyond number, SNARC-like tasks have been used to test spatial mappings of many non-spatial domains, including size, brightness, auditory intensity, and even highly abstract domains like emotional intensity (Holmes, Alcat, & Lourenco, 2019;Macnamara, Keage, & Loetscher, 2018). These results have been widely interpreted as evidence of a "generalized magnitude system" (GMS; Walsh, 2003, p. 484).…”
mentioning
confidence: 99%
“…In his initial proposal for a GMS, Walsh (2003) suggested that one of the "strong predictions" (p. 487) was that the numerical SNARC effect should generalize to other quantitative domains. Accordingly, SNARC and SNARC-like effects have been highlighted as an especially important source of evidence for the putative GMS (Bueti & Walsh, 2009;Macnamara et al, 2018;Walsh, 2015).…”
mentioning
confidence: 99%